Discourse Within the Interactional Space of Literacy Coaching - Valerie Dunham; Dana A. Robertson (Education Sciences)
Reviews of literacy coaching show positive outcomes for teaching and learning, yet also that coaching’s impact varies widely, especially at increased scale. Thus, some scholars argue the quality of coaching interactions may matter more than broad coaching actions (e.g., co-planning, observing). Situated within Habermas’s notion of “public sphere”, we used discourse analysis to examine video-recorded pre- and post-interviews, coaching meetings, and coach retrospective think-aloud protocols of a literacy coach and elementary school teacher who described their partnership as “successful”. We examined participants’ values expressed about coaching; how each participant positioned themselves, each other, and the coaching context; and the nature of the coach–teacher discourse therein to answer the following question: what occurs in the interactional space between a coach and teacher when engaged in coaching meetings? We found four categories of values focused on participatory choice, their sense of connectedness, knowledge development, and their approach to working with/as a coach. Further, participants’ positionings signified agency for both the coach and teachers in the interactional space. While bracketing and leveraging their own authority, the coach’s language choices promoted teachers’ agency within the interactional space, providing insight into how language functions to shape the “public sphere” of coaching interactions.